Fungsi Badan Pertanahan Nasional Dalam Pengawasan Pejabat Pembuat Akta Tanah Di Kabupaten Tanjung Jabung Barat - Masriyani Masriyani (Universitas Batanghari Jambi, 2018)
In the national land Agency Chief Regulation No.1 Year 2006 as modified by regulation the head of BPN number 23-year 2009 on implementation of the provisions of the Government Regulation Number 37 Year 1998, head of the Office of land do coaching and surveillance against a land deed official (PPAT). Starting on the dotted the legal basis and see the development as well as the needs of the ground then for the validity of the ownership of the land, should be are published through the certificate of property rights. For it is necessary supervision against the authorized officials as a PPAT in the deed of the land pembuatak. As for the problems in this research is how the functions of the national land Agency in the construction and supervision of land deed official Tanjung Jabung Barat region. The type of research that is in use is the empirical research. Data on use is the primary data and the data of skunder. Data collection was done through the research library and field research. The research describes the construction and supervision on Land against the head of the Office to do the task in Tanjung Jabung PPAT West, running as it should be in accordance with article 65 of the regulation of the Republic of Indonesia head of BPN No. 1 year 2006 regarding the implementation of the provisions of REGULATION No. 37 Year 1998 Of Regulations Office of the PPAT in coaching and supervision is quite optimal. It can be seen that for the year 2016 year 2017 until the violations perpetrated PPAT decreased. Surveillance against PPAT performed by the Head Office of land is to provide direction to all stakeholders associated with the PPAT's, conducting surveillance over the organisation of the profession of PPAT to keep running in accordance with the direction and the goal, run other actions deemed necessary to ensure the service of PPAT continue to run properly and to conduct surveillance against a PPAT and PPAT in order to run the code of ethics of the profession, the PPAT Tanjung Jabung West land in cooperation with the relevant parties especially the IPPAT code of ethics watchdogs and PPAT.